2009
DOI: 10.1097/mpa.0b013e31818f6bea
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salvia miltiorrhiza on Intercellular Adhesion Molecule 1 Protein Expression in the Lungs of Rats With Severe Acute Pancreatitis or Obstructive Jaundice

Abstract: Salvia miltiorrhiza plays a positive role in the protection of the lungs of SAP and OJ rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Higher IL-18 concentrations are measured in the more severe attacks [16]. As observed in our study, high serum IL-18 concentrations are present in control rodents [15,17]. In the present study, we have shown that pancreatic and pulmonary concentrations of IL-18 have the same profile as the serum concentrations, i.e.…”
Section: Resultssupporting
confidence: 70%
“…Higher IL-18 concentrations are measured in the more severe attacks [16]. As observed in our study, high serum IL-18 concentrations are present in control rodents [15,17]. In the present study, we have shown that pancreatic and pulmonary concentrations of IL-18 have the same profile as the serum concentrations, i.e.…”
Section: Resultssupporting
confidence: 70%
“…There was no marked difference in mortality rate between the time points at 3 and 6 h after operation. At 12 h after operation, only the mortality rate in model control group was significantly higher than that in sham-operated group (P=0.037), and no marked difference in mortality rate was observed among other groups (P>0.05) [19][20][21][22][23].…”
Section: Comparison Of Mortality Ratementioning
confidence: 99%
“…Shamoperated group was performed by the injection of saline solution instead of taurocholate, this is the only difference from the model control group. Fifteen minutes after successful operation, a single dose of Salvia miltiorrhizae injection (0.4 ml/100 g body weight) was given via femoral vein to rats in treated groups while equal volume of physiological saline solution was used in the shamoperated and model control group [19][20][21][22][23].…”
Section: Animal Groupingmentioning
confidence: 99%
See 2 more Smart Citations